The Structure and Tasks of Educational Holdings - Y. A. Maksimova (Russian State Vocational Pedagogical University, 2015)
The analysis carried out by the author at the junction of pedagogy and economics reveals the link between the development of educational system and labor organization in society. On this ground the educational holdings are considered to be the most adequate to the requirements of the modern labor market. The aims of educational holdings are defined along with their advantages and disadvantages. The differences between the educational holding and university complex are pointed out. According to the author, out of the three types of holding organization - regional, industrial and federal - the regional one is most likely to become the dominant innovative educational form. The results of the research analyses can be used both theoretically to study the development prospects of the professional school and practically to establish the alternative educational forms.